The Impact of Organizational Culture on Creativity: The Mediating Role of Knowledge Management (Case Study: Medical Sciences and Health Services University in Bushehr) - Rastgoo, Parvaneh (International Review of Management and Marketing, 2017)
The purpose of the present research was studying the effect of organizational culture on creativity with an emphasis on the mediating role of knowledge management. In terms of purpose, this is a practical research, in terms of data collection this is a descriptive survey research, and the collected data are quantitative (via questionnaire). The statistical population of the present research consisted of 301 people working in educational deputies, research and technology deputies, and cultural and scholastic deputies. From them, 170 individuals were selected as sample size, using Morgan and Krejcie tables, and Stratified Random Sampling method. The data analysis were performed by structural equation modelling (SEM) and Smart PLS software. The results showed a positive and significant effect of organizational culture on the creativity of the employees, organizational culture on knowledge management and finally knowledge management on the creativity of the employees. Keywords: Organizational culture, Knowledge management, Creativity, Creating knowledge. JEL Classifications: D83, M14